Pengaruh Strategi Pembelajaran PQ4R ( Preview, Quetion, Read, Reflect, Recite, Riview) Terhadap Hasil Belajar Biologi Siswa Di SMA N 2Tondano - Yalindua, Aser; Raturandang, Jeffry; Lumbantoruan, Beta Rouli (JSME (Jurnal Sains, Matematika & Edukasi), 2020)
ABSTRACT. Â This study was conducted to determine the effect of the PQ4R learning strategy on student learning outcomes in class XI IPA Tondano NAN 2ND cell subject material in the 2019/2020 school year. This study uses a quasi-experimental method with a Pretest-Posttest research design. The sample in this study was class XI IPA-1 consisting of 20 students as an experimental class who were treated with the PQ4R learning strategy and class XI IPA-2 consisting of 20 students as a control class who were treated with a lecture learning model taken with random sampling techniques. . The average posttest score obtained in the experimental class 88.5 control class was 73.5. The data analysis technique used is the t-test using Liliofers and homogeneous tests. In the t-hypothesis test by calculating the difference between the posttest and the pretest there was -2.02 <9.29> 2.02. Thus, reject h0 and accept h1 based on this it can be concluded that the PQ4R learning strategy affects student learning outcomes in cell material at SMA N 2 Tondano.